Analysis of human factors in wiev of safety at some agricultural companies in Hajdú-Bihar county - Terjék, László (Acta Agraria Debreceniensis, 2009)
The author examined the human social influence factors of the occupational safety and health and number of workers at thirteen different agricultural firms. He’d measured at these enterprises the demographic characteristics and the risk sensibility of farmlabourers at scopes of activities and some related occupational safety and health attitudes from the psychosocial factors. He used questionnaire and personal guided interviews and methodical examinations. He used seven graded Likert-scale (-3...0...+3) (Malhotra, 2005) for qualification of answers. He established that selection by the leaders don’t prefer the special skills. He stated that the examined farm-labourers have got a low risk sensibility, but the statistics of the accidents not certifies it. With the occupational safety and health related attitudes influence the relation to the occupational safety and health, and to comply with OSH rules. It was established that the rate of quasi-accidents is relative high at agricultural workers.